The significance of ERK5 catalytic-independent functions in disease pathways - Le, Nhat-Tu (Frontiers in Cell and Developmental Biology, 2023)
Extracellular signal-regulated kinase 5 (ERK5), also known as BMK1 or MAPK7, represents a recent addition to the classical mitogen-activated protein kinase (MAPK) family. This family includes well-known members such as ERK1/2, c-Jun N-terminal kinase (JNK), and p38 mitogen-activated protein kinase (p38 MAPK), as well as atypical MAPKs such as ERK3, ERK4, ERK7 (ERK8), and Nemo-like kinase (NLK)1-8. Comprehensive reviews available elsewhere provide detailed insights into ERK5, which interested readers can refer to for in-depth knowledge9, 10. The primary aim of this review is to emphasize the essential characteristics of ERK5 and shed light on the intricate nature of its activation, with particular attention to the catalytic-independent functions in disease pathways.